Chemical-bromatological quality and productivity of peanut genotypes (Arachis hipogaea L.) - Barbosa, Jorge Marcos Peniche (2019)
Peanuts (Arachis hipogaea L.) have a great potential for grain production for feed and forage production, being an alternative for producers, as it grows a double product. Grains have excellent quality and contain a greater amount of protein with which to feed the herd. The present study is a cut-off effect study with an application of Stimulate® phytostimulant to determine grain quality and peanut fodder genotype. In the first planting, the peanuts were cultivated under field conditions in a randomized block design in a 4 × 2 × 2 subplot scheme, with four cultivars and two cutting periods, with or without phytostimulant. The cultivars were IAC Tatu ST and Caiana (vertical growth), as well as non-flowering and harvesting seeds. For the second planting, a randomized block design was used with a subplot scheme of 3 × 2 × 2, with three cultivars and 2 cutting periods, with or without phytostimulant. The cultivars were IAC Tatu ST and Caiana (vertical growth) and IAC 503 (prostrate growth). All cultivars contained a high percentage of hay protein in the two plantings. The cultivar IAC 503 was efficient in the production of protein and fiber in the grains in both plantings, demonstrated the potential of protein for animal supplementation, and also presented high grain yield in the summer planting.